Religion and the Science of Human Nature in the Scottish Enlightenment - Mills, R.J.W. author. aut Link
XIV, 334 p. 1 illus.
Keywords: “Robin Mills’ new book is a comprehensive and insightful account of the academic study of religion by philosophers in the Scottish Enlightenment. It is especially valuable for its attention to figures who are not well known today, but who were influential in the eighteenth century." Dr James Foster, University of Sioux Falls Religion and Science are often seen as hostile concepts, but as the example of the Scottish Enlightenment shows, this is not necessarily the case. In Robin Mills’ new book he takes us beyond the headline of David Hume’s alleged atheism and explores the enlightened Scottish conversation about religion. In doing so he shows how the Scottish Enlightenment sought to apply an empirically based social theory to explain religion and its evolution, and the impact this had on the religious views of this significant group of thinkers. It sheds new light on an important moment in intellectual history. Dr Craig Smith, University of Glasgow Absorbing and thoughtful, Robin Mills’s book on the natural history of religion in the Scottish Enlightenment fills a conspicuous gap in the history of ideas. With remarkable erudition and no little finesse, he brings home the originality and distinctiveness of the Scottish endeavour to produce a naturalistic account of religion in the second half of the eighteenth century. What is particularly refreshing about Mills’s study, however, is his unfashionable insistence that this venture represented a rupture with previous approaches to the study of religion, inaugurating a recognisably modern outlook. Dr Niall O’Flaherty, King’s College London “There has been a lot of scholarly interest in the Scottish Enlightenment’s thinking on religion, but surprisingly little has been written on the links between this writing and the Scots’ famous ‘Science of Man’. In this excellent volume Robin Mills sets out to remedy this by offering a survey of the social scientific examination of religion by a range of key Scottish thinkers of the time. Clear, concise, and elegantly written, it is a welcome addition to the literature.” — Craig Smith, Professor of the History of Political Thought, The University of Glasgow, UK This book examines how enlightened Scottish social theorists c.1740 to c.1800 understood the origin and development of religion. Challenging scholarly disregard for the topic, it shows how most prominent thinkers of the Scottish Enlightenment thought deeply about the relationship between religion, human nature and historical change. The Scots viewed this relationship as an important strand within the study of the 'science of human nature' and the 'history of man.' The fruits of this investigation were a sophisticated and innovative account of religious change that is characterized by a striking modernity and naturalism, even by the more devout theorists. The views of the literati surveyed here need to be incorporated into our larger histories of the 'science of religion' as much as they do into our understanding of the social theory of the Scottish Enlightenment. R. J. W. Mills is an Honorary Research Fellow at the Institute of Intellectual History, University of St Andrews, UK. .